Phase Reversal Technique Applied to Fishnet Metalenses - Victor Pacheco-Peña; Igor V. Minin; Oleg V. Minin; Miguel Beruete (International Journal of Antennas and Propagation)
In this work, the fishnet metamaterial is applied to several converging metalenses by combining the zoning, reference phase, and phase reversal techniques. First, the zoning and reference phase techniques are implemented in several metalenses at 55 GHz (λ0=5.45 mm) with a short focal length of 1.5 λ0. Then, the phase reversal technique is applied to these metalenses by switching from a concave to a convex profile in order to change the phase distribution inside of them. The designs are evaluated both numerically and experimentally demonstrating that chromatic dispersion (the shift of the position of the focus at different frequencies) is reduced when using the phase-reversed profiles. It is shown how the position of the focus remains at the same location within a relatively broadband frequency range of ~4% around the design frequency without affecting the overall behaviour of the metalenses. The best performance is achieved with the design that combines both reference phase and phase reversal techniques, with an experimental position of the focus of 1.75 λ0, reduced side lobes, and a power enhancement of 6.5 dB. The metalenses designed here may find applications in situations where a wideband response and low side lobes are required because of the reduced chromatic aberrations of the focus.